Special Digital Repository Practice - Developing a Service-Oriented Database of Cases of Emergency Management at Jinan University. Issue 3 (1st October 2017) - Zhu, Qiandong; Zhong, Yuanxin; Xiao, Liping; Li, Tianzhang; Zhang, Chunxiao; Huang, Yuntao; Wang, Xiaoqiang; Zhang, Xinxing
Abstract: This paper introduces the special digital repository practice at Jinan University, which is the developing a Service-Oriented Database of Cases of Emergency Management (SODCEM). We described the development process of SODCEM, including users' needs analysis, program application, program implementation, metadata definition, development platform selection, users' service and outcome. The practice achieved its primary goal, providing long-term preserved resources for targeted users from emergence management, such as researchers, government officials and even the public. It helped the librarians who attended this project to make great progress on digital resources collection and processing. The practice significantly increased the library reputation on special digital repository, curation and services among the academic community in the university, which enriched the role of the library in the information era and appealed to the targeted user groups. The implementation and relevant experience have implications for academic libraries and other institutions to conduct similar programs.